2018
DOI: 10.1007/s13167-018-0155-5
|View full text |Cite
|
Sign up to set email alerts
|

In glaucoma patients, low blood pressure is accompanied by vascular dysregulation

Abstract: BackgroundThere are many risk factors contributing to glaucomatous optic neuropathy. Beside increased intraocular pressure, vascular factors play a prominent role, particularly low blood pressure (BP), and vascular dysregulation. Both of them are essential components of the Flammer syndrome. The aim of this retrospective study was to evaluate whether in glaucoma patients there is a relationship between vascular dysregulation and the BP.MethodsMedical records of 57 unselected glaucoma patients were retrospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 31 publications
0
21
0
1
Order By: Relevance
“…More details on this calculation can be found in Supplemental Material S2A (see https://doi.org/10.6084/m9.figshare.12738590.v1). Glaucoma subjects were excluded from this analysis because, in these subjects, perfect AR is less safe as an assumption (12,114).…”
Section: Data Analysis-statisticsmentioning
confidence: 99%
“…More details on this calculation can be found in Supplemental Material S2A (see https://doi.org/10.6084/m9.figshare.12738590.v1). Glaucoma subjects were excluded from this analysis because, in these subjects, perfect AR is less safe as an assumption (12,114).…”
Section: Data Analysis-statisticsmentioning
confidence: 99%
“…Compared to normal subjects, glaucoma patients exhibit blood flow abnormalities in vessels of the optic nerve head, 18 retina, 18 retrobulbar tissue, 19 and choroid. 18 , 20 , 21 With limited information regarding autonomic dysfunction involvement, several researchers proposed that ocular vessel disturbances are linked to plasma levels of endothelin-1, 22 systemic blood pressure, 23 , 24 and vasospasm. 25 Autonomic function reflects the effect of parasympathetic nervous system activity on the heart.…”
mentioning
confidence: 99%
“…The analysis of diseases linked to glaucoma genes showed that cardiovascular diseases were most closely associated with glaucoma 50 . Previous research pointed to an abnormal hemorheological pattern in glaucoma patients, with increased plasma viscosity leading to the hypoperfusion of the ophthalmic artery, which can potentially aggravate optic nerve injury 51 . Other research has suggested that peripheral vascular endothelial dysfunction may be related to the progression of glaucoma 52 .…”
Section: Discussionmentioning
confidence: 99%